Feasibility Study Downstream Facility for Bacillus Calmette Guerin (BCG) Project of PT. Biofarma - Adiningrum, Anisa; Sukarno, Subiakto (Journal of Business and Management, 2015)
Abstract. BFM has been constantly striving to discover new vaccines for more than 123 years, in order to eradicate communicable diseases that continue to grow and threaten the humansâ€™ health. Therefore, this research has the objective to conduct a conclusion whether the replacement production line of Bacillus Calmette Guerin (BCG) is feasible or not. Bacillus Calmette Guerin (BCG) is known as freeze-dried vaccine which contains live attenuated of Mycobacterium Bovis, Paris strain. Nowadays the process of production BCG will replace by new technology because of increased demand. Theories and methods in this research are cash flow, Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PBP), and sensitivity analysis. The result of this project indicates the feasibility of the project and the benefit of the project for PT. BFM. Based on the positive NPV, greater IRR when compared with WACC, and shorter payback period when compared with the project economical life, this project is economically feasible.Â Keywords: Cash Flow, NPV, IRR, Payback Period, Sensitivity Analysis